2022
DOI: 10.3390/foods11050689
|View full text |Cite
|
Sign up to set email alerts
|

Cooking and In Vitro Digestion Modulate the Anti-Diabetic Properties of Red-Skinned Onion and Dark Purple Eggplant Phenolic Compounds

Abstract: The intake of phenolic-rich foods is an emerging preventive approach for the management of type 2 diabetes, thanks to the ability of these compounds to inhibit some key metabolic enzymes. In this study, the influence of cooking and in vitro digestion on the α-glucosidase, α-amylase, and dipeptidyl-peptidase IV (DPP-IV) inhibitory activity of red-skinned onion (RSO) and dark purple eggplant (DPE) phenolic fractions was assessed. The applied cooking procedures had different influences on the total and individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Glucosinolates Anti-inflammatory activity [83] Eggplant (Solanum melongena) Phenolic compounds Antidiabetic activity [84] Solasodine Anticancer activity [85] Ginger (Zingiber officinale) and mulberry fruit (Morus alba) Extract Brain health and oxidative stress [86] Grape (Vitis spp.) Phenols, proanthocyanididns Gut health [87][88][89] Hemp grain (Cannabis sativa) Phenolics Antioxidant activity [90,91] Lettuce (Lactuca sativa) Polyphenols Antidiabetic activity [92] Manchurian walnut (Juglans mandshurica) Hydrolyzed peptides Antidiabetic activity [93] Oats (Avena sativa) Phenolics Antioxidant, prebiotic [12,94] Olive oil (Olea europaea) Polyphenols Cardiovascular activity [95] Oolong tea (Camellia sinensis) (−)-epigallocatechin Gut health [96] Quinoa (Chenopodium quinoa) Bioactive peptides Antidiabetic and anticancer [97,98] Seaweed (Porphyra tenera) Extract Gut health, antioxidant [99,100] Sorghum (Sorghum bicolor) Phenolic Anticancer activity [101,102] Soybean (Glycine max) Isoflavones Anticancer activity [103,104] Isoflavonoid Insulinotropic activity [105] Oolong tea (Camellia sinensis)…”
Section: Cruciferous Vegetablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucosinolates Anti-inflammatory activity [83] Eggplant (Solanum melongena) Phenolic compounds Antidiabetic activity [84] Solasodine Anticancer activity [85] Ginger (Zingiber officinale) and mulberry fruit (Morus alba) Extract Brain health and oxidative stress [86] Grape (Vitis spp.) Phenols, proanthocyanididns Gut health [87][88][89] Hemp grain (Cannabis sativa) Phenolics Antioxidant activity [90,91] Lettuce (Lactuca sativa) Polyphenols Antidiabetic activity [92] Manchurian walnut (Juglans mandshurica) Hydrolyzed peptides Antidiabetic activity [93] Oats (Avena sativa) Phenolics Antioxidant, prebiotic [12,94] Olive oil (Olea europaea) Polyphenols Cardiovascular activity [95] Oolong tea (Camellia sinensis) (−)-epigallocatechin Gut health [96] Quinoa (Chenopodium quinoa) Bioactive peptides Antidiabetic and anticancer [97,98] Seaweed (Porphyra tenera) Extract Gut health, antioxidant [99,100] Sorghum (Sorghum bicolor) Phenolic Anticancer activity [101,102] Soybean (Glycine max) Isoflavones Anticancer activity [103,104] Isoflavonoid Insulinotropic activity [105] Oolong tea (Camellia sinensis)…”
Section: Cruciferous Vegetablesmentioning
confidence: 99%
“…Red-skinned onion and purple eggplant are other sources of phenolic compounds with possible antidiabetic properties. Cattivelli et al [84] found that cooking increased the bioavailability of phenolic compounds from the onion and eggplant, which improves their action against the risks of type 2 diabetes. The study found that certain compounds in the onion inhibited three of the key enzymes that are involved in diabetes pathogenesis [84].…”
Section: Antidiabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, onion can be consumed, in the daily diet, either raw or cooked through different methods such as grilling and frying, which are the two most usual cooking procedures applied to onion. Several studies evidenced that heat treatments during cooking may modify the phenolic profile and structures of vegetables foods resulting in a different and sometimes higher bioactivity, and improved bioaccessibility after in vitro gastrointestinal digestion 1,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies evidenced that heat treatments during cooking may modify the phenolic profile and structures of vegetables foods resulting in a different and sometimes higher bioactivity and improved bioaccessibility after in vitro gastro-intestinal digestion. 1,6,7 Additionally, these modified compounds undergo an ulterior transformation when they enter the colon, where they can feed the colon microbiota to foster beneficial bacteria and inhibit opportunis-tic microbes. 8 Unfortunately, this improvement can also have the opposite impact on the colon microbiota, adversely affecting sensitive beneficial bacteria, such as bifidobacteria.…”
Section: Introductionmentioning
confidence: 99%